Extended Stern Model - Pradhan, Rangadhar; Mitra, Analava; Das, Soumen (Journal of Applied Solution Chemistry and Modeling, 2012)
In this paper, a theoretical approach of extended Stern model is formulated to represent the electric double layer (EDL) for biochemical as well as biological samples. The existing Stern model is used for several decades to describe the phenomena of electric double layer of electrode/electrolyte interface. In the conventional stern model the double layer which is formed between the electrode and electrolyte interface is described by double layer capacitance. Using the existing Stern model, the equivalent circuit model is not valid for electrical double layer capacitance of electrode/electrolyte interface in Î² dispersion range. The protein molecules form chemical coupling and chemical adsorption along with classical ionic bonding with gold electrodes. Thus, the compactness of EDL decreases and the double layer capacitance is replaced by a constant phase element (CPE). In the present paper, a three-electrode based ECIS device was used to measure the impedance of various enzymatic solutions for practical realization of theoretical approach. The results obtained from experimental work, were simulated by equivalent circuit simulator, ZsimpWin to validate the extended Stern model by comparing Ï‡2 value. Finally the electrical parameters were extracted and compared for Stern model and extended Stern model. The results obtained by practical experiment and equivalent circuit simulation showed the effectiveness of extended Stern model over Stern model.